Effects of hot-air drying on physicochemical characteristics, flavour profiles and sensory acceptance of Citrus hystrix and Etlingera elatior jack - Juhari, Nurul Hanisah (2012)
Herbs and spices play important roles in Malay cuisine. The usage of kaffir lime (C. hystrix)leaves and torch ginger (E. elatior) are not only limited to the addition of flavour and enhancement of palatability of food but they also act as antioxidants. Both herbs were grown for both flavouring and medicinal purposes. However, this herb is highly perishable in nature, have short shelf life and deteriorate rapidly after harvesting that leads to loss of flavour and quality. So, drying is an important technology for preserving the product quality and also preventing the spoilage of the product during storage. Thus, this study was conducted to optimize the effects of hot-air drying conditions (drying time, drying temperature and loading capacity) on physicochemical characteristics (moisture content, water activity, texture and colour) of C. hystrix and E. elatior that could be used for a high food grade spicing material. Secondly, the flavour profiles of C. hystrix and E. elatior were determined between fresh and optimally dried herbs. The herbs inclusion/infusion parameters levels (size, temperature and concentration of herbs) on sensory acceptance of Vichyssoise soup and sorbet were also optimized. The results showed that the best response for torch ginger, within the range studied, was reached when the drying time was 4.1 h, the drying temperature, 79 °C and loading capacity, 0.7 kg/m2 respectively. On the other hand, the overall optimum conditions that resulted in desirable dried kaffir lime leaves, was achieved when the drying time was 4.9 h, the drying temperature, 60 °C and loading capacity, 1.4 kg/m2. No significant (p>0.05) difference was found between the experimental and predicted values, thus ensuring the adequacy of the response surface models employed for describing the effects of hot-air drying on physicochemical properties of torch ginger and kaffir lime leaves. At the second stage, liquid-liquid solvent extraction was employed to extract flavour compounds of the samples which were analyzed using Gas Chromatography (GC) and Gas Chromatography-Mass Spectrometry (GC-MS) with DB-5, BPX-5 as well as Quadrex007CW columns. The finding from GC and GC-MS revealed that fresh torch ginger contained 91 volatile compounds while optimally dried torch ginger contained 104 volatile compounds using Quadrex007CW column. However, only 54 volatile compounds of fresh torch ginger and 147 volatile compounds of optimally dried torch ginger were obtained using DB-5 column. The major aroma components in both fresh and optimally dried torch ginger were alcohol, ester, alkane, carboxylic acid, ketone and aldehyde. A total of 45 compounds were identified in fresh kaffir lime leaves as compared to 41 compounds in optimally dried kaffir lime leaves using BPX-5 column. However, a total of 66 compounds were determined in fresh kaffir lime leaves and 40 compounds in optimally dried kaffir lime leaves using DB-5 column. Monoterpenes and sesquiterpenes were found to be major components. Finally, the herbs inclusion/infusion parameters levels [size of herbs (2-100 mm), concentration of herbs (3-15 g/L)and temperature of inclusion (25-100 °C)] in different types of food systems (liquid and semi solid) were determined. Sensory evaluations using 50 untrained panelists were utilized to assess colour, aroma, taste and overall acceptability of products. The results from sensory valuation showed that vichyssoise soup flavoured with optimally dried C. hystrix leaves were more highly preferred by panelist compared to vichyssoise soup flavoured with optimally dried E. elatior while sorbet flavoured with optimally dried C. hystrix were highly preferred by panelist compared to sorbet flavoured with optimally dried E.elatior. This study has significantly contributed to the establishment of standardized measurements for the amount of herbs required for various kinds of foods. Potentially, this study also yields herbs that reaches international specification standard and enables worldwide export of Malaysian herbs.